First Principles Study of Structural, Electronic and Mechanical Properties of LiBeF3 under Pressure Effect - Kshetri, Kshitiz; Chaudhary, Uchit; Tamang, Ependra; Dangal, Basanta Raj; Acharya, Abhinash; KC, Kumar; Singh Thakuri, Bhairab Sundar (Academic Journal of Sukuna, 2025)
The structural, electronic and elastic properties of LiBeF3 under high pressure were investigated using the density functional theory. The optimized lattice constant and the bulk modulus of elasticity at 0 GPa were obtained as 3.500 Å and 104.79 GPa, respectively, which are in good agreement with the previously available results. To study the effect of pressure, variable-cell relaxation (vc-relax) calculations were performed at different pressures ranging from 0 to 50 GPa. The mechanical properties of LiBeF3 reveal that it is mechanically stable at the chosen pressures of 0, 10, 20, 30, 40 and 50 GPa. The Pugh’s ratio and Poisson’s ratio for LiBeF3 were consistent throughout the increase in pressure, suggesting the brittle nature and dominance of ionic bonding in LiBeF3. The electronic band gap of LiBeF3 at 0 GPa was found to be 7.46 eV with indirect nature. On further increasing the pressure, the band gap of the LiBeF3 crystal increased while maintaining its indirect nature. The Young’s modulus, shear modulus and anisotropy factor of LiBeF3 were also investigated and presented in this paper.